The Effect of Incubation Temperature on Deviations of Pholidosis and Malformations in Grass Snake Natrix natrix (L. 1758) and Sand Lizard Lacerta agilis (L. 1758) - Idrisova, L A (KnE Life Sciences, 2018)
This paper considers morphological deviations of reptiles and the influence of incubation temperature on this phenomenon. 28 types of pholidosis deviations and 5 types of malformations were observed in juvenile grass snakes. Sand lizards demonstrated 26 types of deviations and 11 types of malformations. The most common malformations in both species were spine and tail deformations. Hatchlings which were incubated at extremely high temperatures were characterized by the largest spectrum and the highest frequency of deviations and malformations. Reptiles with spine deformations had a great number of deviant ventral scales.